Cover Feature: Enhanced Cycling Performance for Lithium–Sulfur Batteries by a Laminated 2D g‐C3N4/Graphene Cathode Interlayer (ChemSusChem 1/2019). Issue 1 (27th December 2018) - Qu, Long; Liu, Pei; Yi, Yikun; Wang, Tao; Yang, Pu; Tian, Xiaolu; Li, Mingtao; Yang, Bolun; Dai, Sheng
Abstract : The Cover Feature shows a 2‐dimensional g‐C3 N4 /graphene sheet complex interlayer for a sulfur/carbon cathode. The thin barrier layer with the laminated‐structure channels acts likes a shark net to block the polysulfide species (Li2 Sx, 2< x ≤8, the big sharks) shuttling via physical and chemical interactions, but also to protect lithium‐ion (Li +, the little fishes) migrating from the cathode to the anode. More information can be found in the Full Paper by L. Qu et al. onpage 213 in Issue 1, 2019 (DOI:10.1002/cssc.201802449 ).